Telecom C-band photon emission from (In,Ga)As quantum dots generated by filling nanoholes in In0.52Al0.48As layers - Deutsch, D.; Buchholz, C.; Zolatanosha, V.; Jöns, K. D.; Reuter, D. (AIP Advances)
We present the fabrication of strain-free quantum dots in the In0.53Ga0.47As/In0.52Al0.48As-system lattice matched to InP, as future sources for single and entangled photons for long-haul fiber-based quantum communication in the optical C-band. We achieved these quantum dots by local droplet etching via InAl droplets in an In0.52Al0.48As layer and subsequent filling of the holes with In0.53Ga0.47As. Here, we present detailed investigations of the hole morphologies measured by atomic force microscopy. Statistical analysis of a set of nanoholes reveals a high degree of symmetry for nearly half of them when etched at optimized temperatures. Overgrowth with 50–150 nm In0.52Al0.48As increases their diameter and elongates the holes along the [01̄1]-direction. By systematically scanning the parameter space, we were able to fill the holes with In0.53Ga0.47As, and by capping the filled holes and performing photoluminescence measurements, we observe photoluminescence emission in the O-band up into the C-band depending on the filling height of the nanoholes.
Keywords: General Physics and Astronomy

Modeling nonlinear optical interactions of focused beams in bulk crystals and thin films: A phenomenological approach - Spychala, Kai J.; Amber, Zeeshan H.; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Coherent nonlinear optical μ-spectroscopy is a frequently used tool in modern material science as it is sensitive to many different local observables, which comprise, among others, crystal symmetry and vibrational properties. The richness in information, however, may come with challenges in data interpretation, as one has to disentangle the many different effects like multiple reflections, phase jumps at interfaces, or the influence of the Guoy-phase. In order to facilitate interpretation, the work presented here proposes an easy-to-use semi-analytical modeling Ansatz, which bases upon known analytical solutions using Gaussian beams. Specifically, we apply this Ansatz to compute nonlinear optical responses of (thin film) optical materials. We try to conserve the meaning of intuitive parameters like the Gouy-phase and the nonlinear coherent interaction length. In particular, the concept of coherence length is extended, which is a must when using focal beams. The model is subsequently applied to exemplary cases of second- and third-harmonic generation. We observe a very good agreement with experimental data, and furthermore, despite the constraints and limits of the analytical Ansatz, our model performs similarly well as when using more rigorous simulations. However, it outperforms the latter in terms of computational power, requiring more than three orders less computational time and less performant computer systems.
Keywords: General Physics and Astronomy

Time-resolved pump–probe spectroscopic ellipsometry of cubic GaN. I. Determination of the dielectric function - Baron, Elias; Goldhahn, Rüdiger; Espinoza, Shirly; Zahradník, Martin; Rebarz, Mateusz; Andreasson, Jakob; Deppe, Michael; As, Donat Josef; Feneberg, Martin (Journal of Applied Physics)
An ultra-fast change of the absorption onset for zincblende gallium-nitride (zb-GaN) (fundamental bandgap: 3.23 eV) is observed by investigating the imaginary part of the dielectric function using time-dependent femtosecond pump–probe spectroscopic ellipsometry between 2.9 and 3.7 eV. The 266 nm (4.66 eV) pump pulses induce a large electron–hole pair concentration up to 4×1020cm−3, which shift the transition energy between conduction and valence bands due to many-body effects up to ≈500 meV. Here, the absorption onset increases due to band filling while the bandgap renormalization at the same time decreases the bandgap. Additionally, the absorption of the pump-beam creates a free-carrier profile within the 605 nm zb-GaN layer with high free-carrier concentrations at the surface, and low concentrations at the interface to the substrate. This leads to varying optical properties from the sample surface (high transition energy) to substrate (low transition energy), which are taken into account by grading analysis for an accurate description of the experimental data. For this, a model describing the time- and position-dependent free-carrier concentration is formulated by considering the relaxation, recombination, and diffusion of those carriers. We provide a quantitative analysis of optical experimental data (ellipsometric angles Ψ and Δ) as well as a plot for the time-dependent change of the imaginary part of the dielectric function.
Keywords: General Physics and Astronomy

On the accuracy, stability and computational efficiency of explicit last-stage diagonally implicit Runge–Kutta methods (ELDIRK) for the adaptive solution of phase-field problems - Westermann, Hendrik; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Threshold photoelectron spectroscopy and dissociative photoionization of benzonitrile - Kamer, Jerry; Schleier, Domenik; Donker, Merel; Hemberger, Patrick; Bodi, Andras; Bouwman, Jordy (Physical Chemistry Chemical Physics)
The seven parallel dissociative ionization channels of benzonitrile yield highly stable fragment ions with commensurate abundance, underlining the potential role of the benzonitrile cation as hub species in the interstellar medium.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Phase sensitivity of spatially broadband high-gain SU(1,1) interferometers - Scharwald, D.; Meier, T.; Sharapova, P. R. (Physical Review Research)
Keywords: General Physics and Astronomy

Phase sensitivity of spatially broadband high-gain SU(1,1) interferometers - Scharwald, Dennis; Meier, T.; Sharapova, P. R. (Physical Review Research)
Keywords: General Physics and Astronomy

Hall mobilities and sheet carrier densities in a single LiNbO3 conductive ferroelectric domain wall - Beccard, Henrik; Beyreuther, Elke; Kirbus, Benjamin; Seddon, Samuel D.; Rüsing, Michael; Eng, Lukas M. (Physical Review Applied)
In the last decade, conductive domain walls (CDWs) in single crystals of the uniaxial model ferroelectric lithium niobate (LiNbO3; LNO) have been shown to reach resistances more than 10 orders of magnitude lower than the resistance of the surrounding bulk, with charge carriers being firmly confined to sheets with a width of a few nanometers. LNO is thus currently witnessing increased attention because of its potential in the design of room-temperature nanoelectronic circuits and devices based on such CDWs. In this context, the reliable determination of the fundamental transport parameters of LNO CDWs, in particular the 2D charge carrier density n2D and the Hall mobility μH of the majority carriers, is of great interest. In this contribution, we present and apply a robust and easy-to-prepare Hall-effect measurement setup by adapting the standard four-probe van der Pauw method to contact a single, hexagonally shaped domain wall that fully penetrates the 200-μm-thick LNO bulk single crystal. We then determine n2D and μH for a set of external magnetic fields B and prove the expected cosinelike angular dependence of the Hall voltage. Lastly, we present photoinduced-Hall-effect measurements of one and the same DW, by determining the impact of super-band-gap illumination on n2D.
Keywords: General Physics and Astronomy

Chirped Bloch-harmonic oscillations in a parametrically forced optical lattice - Ali, Usman; Holthaus, Martin; Meier, Torsten (Physical Review Research)
Keywords: General Physics and Astronomy

Resonance enhanced multiphoton ionization detection of aromatics formation in fuel-rich flames - Kasper, Tina; Hansen, Nils (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry